The dynamics, analysis, and sustainable management of phosphorus in muck soils: a review - Phuyal, Dinesh; Nair, Vimala D. (Frontiers in Environmental Science, 2025)
Muck soils (Histosols) are vital and highly productive ecosystems for agriculture. However, managing phosphorus in these organic-rich systems presents a major challenge. Decades of fertilization have created large legacy phosphorus accumulation, while drainage and cultivation have altered soil pH increasing phosphorus immobilization by calcium interaction. Standard soil tests developed for mineral soils consistently fail to predict crop phosphorus needs in muck soils because their chemical extractants are often neutralized by high organic matter, and results confounded by dominant biological phosphorus cycling leading to inaccurate recommendations. This review provides new insights into how phosphorus behaves in muck soils and highlights the limitations of current soil tests in capturing this complexity. Bridging this gap is essential for both agronomic efficiency and environmental protection. The key recommendation is to move away from universal extractants toward the development of robust, regionally calibrated assessment tools. These tools must integrate key soil properties, such as organic matter, pH, and phosphorus-binding elements, to effectively guide sustainable nutrient stewardship in these vulnerable ecosystems.